Jeanette Winterson’s The Stone Gods as a Feminist Cyborg Story Cyborg Story - Tomasz Dobrogoszcz (Zagadnienia Rodzajów Literackich)
Jeanette Winterson’s 2007 novel The Stone Gods is an admonitory tale about human environmental irresponsibility: in a highly gendered narrative the novelist demonstrates how the patriarchal domination inherent in human civilization leads to the destruction of the planet. Drawing upon the theoretical framework provided by posthumanist studies, especially the feminist perspective of Donna Haraway, N. Katherine Hayles and Rosi Braidotti, the article interprets Winterson’s novel as a critique of the masculinist domination of human culture. It shows The Stone Gods as one of Haraway’s “feminist cyborg stories”, demonstrating that a female robot might prove to be a model for new human subjectivity which could lead our civilization away from the path towards self-destruction.